2010
DOI: 10.1002/mrm.22335
|View full text |Cite
|
Sign up to set email alerts
|

An automated method for nonparametric kinetic analysis of clinical DCE‐MRI data: Application to glioblastoma treated with bevacizumab

Abstract: Here, we describe an automated nonparametric method for evaluating gadolinium-diethylene triamine pentaacetic acid (Gd-DTPA) kinetics, based on dynamic contrast-enhanced-MRI scans of glioblastoma patients taken before and after treatment with bevacizumab; no specific model or equation structure is assumed or used. Tumor and venous blood concentration-time profiles are smoothed, using a robust algorithm that removes artifacts due to patient motion, and then deconvolved, yielding an impulse response function. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 28 publications
5
40
0
Order By: Relevance
“…6). Model-free methods included the visual assessment of spatiotemporal enhancement patterns in multiple sclerosis lesions (Kermode et al, 1990; Gaitán and Shea, 2011; Shinohara et al, 2011), calculation of semi-quantitative parameters from the signal enhancement (Wardlaw et al, 2008; Wardlaw et al, 2009; Starr et al, 2003; Starr et al, 2009; Topakian et al, 2010; Brandt et al, 2008; Su et al, 1998; Miyati et al, 1997; Wang et al, 2006; Mills et al, 2009; Provenzale et al, 2006; Wilkinson et al, 2006) and/or contrast agent concentration (Budde et al, 2012; Armitage et al, 2011) curves, and model-free deconvolution (Singh et al, 2007; Larsson et al, 2009; Cramer et al, 2014; Haris et al, 2008a,c; Awasthi et al, 2012; Ferl et al, 2010; Larsen et al, 2013; Gupta et al, 2012). The most commonly used pharmacokinetic models were the conventional Tofts model (Singh et al, 2007; Jelescu et al, 2011; Li et al, 2000; Noseworthy and Bray, 2000; Haris et al, 2008a,b,c; Thompson et al, 2012; Manuchehri et al, 2007; Cha et al, 2006; Harrer et al, 2004; Zhu et al, 2000; Ferl et al, 2010; Jia et al, 2013; Gupta et al, 2012), the modified Tofts model (Li et al, 2012; Ali et al, 2010; Hoff et al, 2012; Aryal et al, 2014; Wei et al, 2011; Awasthi et al, 2012; Bagher-Ebadian et al, 2012; Cao et al, 2009; Chu et al, 2012; Harrer et al, 2004; Zhang et al, 2012; Ingrisch et al, 2012; Song et al, 2011; Larsson et al, 2013), the Patlak model (Larsson et al, 2009; Cramer et al, 2014; Abo-Ramadan et al, 2009; Durukan et al, 2009; Ewing et al, 2003; Nagaraja et al, 2010; Taheri et al, 2009; Krueck et al, 1994; Vidarsson et al, 2009…”
Section: Resultsmentioning
confidence: 99%
“…6). Model-free methods included the visual assessment of spatiotemporal enhancement patterns in multiple sclerosis lesions (Kermode et al, 1990; Gaitán and Shea, 2011; Shinohara et al, 2011), calculation of semi-quantitative parameters from the signal enhancement (Wardlaw et al, 2008; Wardlaw et al, 2009; Starr et al, 2003; Starr et al, 2009; Topakian et al, 2010; Brandt et al, 2008; Su et al, 1998; Miyati et al, 1997; Wang et al, 2006; Mills et al, 2009; Provenzale et al, 2006; Wilkinson et al, 2006) and/or contrast agent concentration (Budde et al, 2012; Armitage et al, 2011) curves, and model-free deconvolution (Singh et al, 2007; Larsson et al, 2009; Cramer et al, 2014; Haris et al, 2008a,c; Awasthi et al, 2012; Ferl et al, 2010; Larsen et al, 2013; Gupta et al, 2012). The most commonly used pharmacokinetic models were the conventional Tofts model (Singh et al, 2007; Jelescu et al, 2011; Li et al, 2000; Noseworthy and Bray, 2000; Haris et al, 2008a,b,c; Thompson et al, 2012; Manuchehri et al, 2007; Cha et al, 2006; Harrer et al, 2004; Zhu et al, 2000; Ferl et al, 2010; Jia et al, 2013; Gupta et al, 2012), the modified Tofts model (Li et al, 2012; Ali et al, 2010; Hoff et al, 2012; Aryal et al, 2014; Wei et al, 2011; Awasthi et al, 2012; Bagher-Ebadian et al, 2012; Cao et al, 2009; Chu et al, 2012; Harrer et al, 2004; Zhang et al, 2012; Ingrisch et al, 2012; Song et al, 2011; Larsson et al, 2013), the Patlak model (Larsson et al, 2009; Cramer et al, 2014; Abo-Ramadan et al, 2009; Durukan et al, 2009; Ewing et al, 2003; Nagaraja et al, 2010; Taheri et al, 2009; Krueck et al, 1994; Vidarsson et al, 2009…”
Section: Resultsmentioning
confidence: 99%
“…Non-parametric approaches (50, 51) include measuring the slope of the rising portion of the curve, measuring the area under the curve at a fixed time point and measuring the maximum and equilibrium portions of the curve. In the parametric approaches, the contrast agent transport phenomena in the highly complex microenvironment have been simplified using pharmacokinetic approaches for DCE-MRI assessment.…”
Section: Application Of Mr Physics To Glioblastomamentioning
confidence: 99%
“…During the 1990’s, Rosen and colleagues at Massachusetts General Hospital demonstrated that diameters of tubes or vessels containing susceptibility-inducing agents could be differentiated by their magnetic susceptibility and that using a combination of gradient-echo (T2* sensitive) and spin-echo (T2 sensitive) MR imaging techniques could provide a voxel-by-voxel estimate of relative vessel diameters in tissue (41, 47-51). By use of a simultaneous gradient-echo spin-echo image acquisition, vessel caliber MRI is performed by measuring the changes in R2* and R2, respectively, from the first past of the contrast agent (Figure 3f).…”
Section: Application Of Mr Physics To Glioblastomamentioning
confidence: 99%
“…DATforDCEMRI [25] is an R package tool which allows performing kinetic deconvolution analysis [32] and visualizing the resulting pixel-wise parametric maps. Like DcemriS4, this software package requires an end-user training in R programming environment.…”
Section: Introductionmentioning
confidence: 99%